2016
DOI: 10.1111/jfs.12287
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of Microbial Contamination on Restaurant Nonfood‐Contact Surfaces

Abstract: Foodborne illnesses are a significant public health concern as they cause approximately 48 million illnesses per year in the U.S.A. It is important to identify and control potential sources of microbial contamination in restaurants to reduce the number of foodborne illnesses. In this study, we aimed to measure microbial contamination on nonfood‐contact surfaces in restaurants. These surfaces include tables, chairs, highchairs and booster seats. We found the highest levels of total microbial contamination and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The largest proportion of contamination was found in the samples obtained from the tables (50%), which was due to the tables' proximity to food, which contributes to the spread of foodborne illnesses. these results were agreed by Galie et al,2018; Jamal et al,2018; Patel et al,2017 [13][14][15], which shed light on the number of bacteria present on surfaces in contact with food in an indirect way, and this contamination may be attributed to contaminated tools used to clean these surfaces. While the results showed that the percentage of contamination from spoons was the lowest (34.37%) because most restaurants during the study period (Corona Virus) relied on the use of single-use plastic spoons.…”
Section: Coliform Contamination In Samplessupporting
confidence: 76%
“…The largest proportion of contamination was found in the samples obtained from the tables (50%), which was due to the tables' proximity to food, which contributes to the spread of foodborne illnesses. these results were agreed by Galie et al,2018; Jamal et al,2018; Patel et al,2017 [13][14][15], which shed light on the number of bacteria present on surfaces in contact with food in an indirect way, and this contamination may be attributed to contaminated tools used to clean these surfaces. While the results showed that the percentage of contamination from spoons was the lowest (34.37%) because most restaurants during the study period (Corona Virus) relied on the use of single-use plastic spoons.…”
Section: Coliform Contamination In Samplessupporting
confidence: 76%
“…Furthermore, foods can be subjected to cross-contamination by bacteria and foodborne viruses from clothing (apron) of the food handlers, and utensils or crockeries used in food preparation (Alves et al, 2021). Food contact surfaces that are not directly associated with food preparation but with serving and consumption have also been implicated to be contaminated with numerous microorganisms at higher levels like the cleaning clothes for the cleaning of serving tables or wiping plates, seating chairs and tables, serving trays, food holding spatulas, drinking glasses, and spoons (Patel et al, 2017;Giwa et al, 2021). An estimated 27% of outbreaks by foodborne pathogens are resulted from contaminated kitchen utensils, while 97% of foodborne illnesses are due to improper food handling practices in restaurants and at home (Tenna et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, da Silva et al [4], reported that S. aureus was transferred to stainless steel and polyethylene immediately upon contact with meat cubes and that populations increased from 3 to 8 log cycles within 24 hours at 20°C. Restaurant nonfood contact surfaces including tables, chairs, highchairs, booth seats and booster seats were found to have over 100 colony forming units per 100 cm 2 indicating the need for more information on their possible role in food cross contamination [5].…”
Section: Introductionmentioning
confidence: 99%